High-Resolution, Motion-Corrected, Volume-Fused OCT for Investigating Longitudinal Changes in Subretinal Drusenoid Deposits in Intermediate AMD - Won, Jungeun; Yaghy, Antonio; Ploner, Stefan; Kaiser, Stephanie; Girgis, Jessica M.; Hwang, Yunchan; Jamil, Muhammad Usman; Maier, Andreas; Waheed, Nadia K.; Fujimoto, James G. (Translational Vision Science & Technology, 2025)
Purpose: To demonstrate high-resolution, motion-corrected, volume-fused optical coherence tomography (OCT) for assessing longitudinal changes in macular dot form subretinal drusenoid deposits (SDDs). Methods: Six consecutive isotropic volume raster scans over 6 × 6 mm (500 × 500 A-scans) were acquired using a high-resolution (2.7 μm axial resolution) spectral domain OCT prototype instrument. OCT volumes were computationally motion-corrected and fused. The distribution and longitudinal changes in dot SDDs were evaluated using en face OCT in a 50-μm-thick slab, from 27 μm above Bruch’s membrane. Results: Computational motion correction and volume fusion methods improve visibility of small en face features and compensate for motion artifacts to facilitate longitudinal assessment. In total, 326 SDDs were identified in a representative series of four eyes from four patients with intermediate age-related macular degeneration (AMD) and assessed with a 3-to 12-month follow-up. Of the SDDs, 85.3% remained stable over the follow-up, while 9.8% regressed, 3.4% fused, and 1.5% new SDDs appeared. Conclusions: Computational motion correction and volume fusion combined with high-resolution OCT B-scans and en face slabs facilitate visualization and longitudinal tracking of focal pathologies, such as SDDs. Translational Relevance: The methods presented have the potential to improve OCT analysis of focal features, such as quantification of SDDs and other AMD biomarkers.
CRIS-Team Scopus Importer:2025-06-27
Keywords: age-related macular degeneration; en face slab; motion correction; optical coherence tomography; subretinal drusenoid deposits